2017
DOI: 10.3390/atmos8120231
|View full text |Cite
|
Sign up to set email alerts
|

Practical Field Calibration of Portable Monitors for Mobile Measurements of Multiple Air Pollutants

Abstract: Abstract:To reduce inaccuracies in the measurement of air pollutants by portable monitors it is necessary to establish quantitative calibration relationships against their respective reference analyser. This is usually done under controlled laboratory conditions or one-off static co-location alongside a reference analyser in the field, neither of which may adequately represent the extended use of portable monitors in exposure assessment research. To address this, we investigated ways of establishing and evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 40 publications
1
15
0
Order By: Relevance
“…Formal environmental sensing data have generally been considered expensive and inadequate for capturing the spatial and temporal dynamics required in environmental monitoring. This is due to static and sparse coverage of stations (Kumar et al, 2015;Little et al, 2016). This perception was confirmed in our research.…”
Section: Formal and Informal Environmental Sensing Datasupporting
confidence: 86%
“…Formal environmental sensing data have generally been considered expensive and inadequate for capturing the spatial and temporal dynamics required in environmental monitoring. This is due to static and sparse coverage of stations (Kumar et al, 2015;Little et al, 2016). This perception was confirmed in our research.…”
Section: Formal and Informal Environmental Sensing Datasupporting
confidence: 86%
“…This test involved the following sensors: sensor B, sensor C and sensor F. The BC sensor A was not involved in this mobility tests because studies (Ezani et al, 2018;Lin et al, 2017) have already demonstrated its ability to perform mobile measurements. Fig.…”
Section: Mobility/reproducibility Testmentioning
confidence: 99%
“…Pairwise strategies a) Reference-based pairwise: Relatively few papers address methodological issues related to reference-based pairwise strategies, as this approach is the closest to a "traditional" calibration approach with measurement standards. Primarily, reference instruments may be directly co-located in the field with non-reference instruments to achieve their calibration [38] [41] [42] [54] [55].…”
Section: Calibration Relationshipsmentioning
confidence: 99%